Perancangan Antarmuka Pengguna Aplikasi Penjualan menggunakan Goal-Directed Design pada CV Gamma Scientific Biolab - Siti Nur Ayni; Ismiarta Aknuranda; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
CV Gamma Scientific Biolab is a distributor company of equipment and chemical material that wants to develop mobile-based sales applications to make it easier for customers to find and order products in their companies. To make good sales applications, it is necessary to design a good user interface too. Therefore, this research aims to design the user interface of the sales application CV Gamma Scientific Biolab using the five phases Goal-Directed Design method. In the research phase, preliminary data obtained about the design reference and the goals that users want to achieve. In the modeling phase, the results are user modeling and workflow consists of persona and BPMN. In the requirements definition phase, the results are a list of user requirements. In the framework phase, the result are a list of functional elements and wireframe design. In the refinement phase, the result are prototype and usability testing of the user interface. The user interface of sales application is tested using usability testing with Nielsen's quality component of learnability, efficiency, errors, and satisfaction. The results of learnability aspect show that user interface design is very easy to learn when the first used. On the efficiency test results, the completion time of one task was only 14.29 seconds. There were five errors made during testing with and the error rate is 0.22. While the system usability scale (SUS) questionnaire results received 77.88 average value, means that the design is excellent and acceptable for the user.